The greenway as a means to recover valley floor areas: A proposal for the Mandacarú stream, Maringá, Paraná State, Brazil - doi: 10.4025/actascitechnol.v34i4.12529 - Barbosa, Leonardo Cassimiro; De Angelis, Bruno Luiz Domingos (Acta Scientiarum. Technology, 2012)
This study proposes to recover the Mandacarú Stream, located in the city of Maringá, Paraná State, Brazil by developing a greenway. The stream in question has been extremely degraded, principally by human activity. The proposed methodology begins with preparing a scenario for the valley floor with a greenway in place. This is followed by an investigation of the corridor´s ecological and cultural variables, taking a holistic view to synthesise and diagnose the information collected. Guidelines for recovering the valley floor and developing the greenway are then drawn up to direct the preparation of the final plan. As a result, the principal environmental impacts that undermine the quality of the study area were surveyed, such as erosion, loss of riparian vegetation, illegal sewage connections and lack of environmental education. A list of guidelines was developed for recovering and conserving the area, in combination with the development of a greenway along the valley floor. It is hoped that these guidelines can assist a future intervention at this location and that the proposed method can be used as the basis for the recovery of other urban valley floors.